Pengaruh Level Pupuk Organik Cair Top G2 Terhadap Produksi Bahan Segar dan Bahan Kering Serta Bahan Organik Rumput Gajah Mini (Pennisetum Purpureum Cv. Mott) Panen Kedua - Tjadu Hina, Anggi N. C.; Nastiti, Herayanti Panca; Osa, Dominggus Benyamin; Sulistijo, Edi Djoko (Animal Agricultura, 2025)
This study was carried out with the aim of determining the effect of applying TOP G2 organic liquid fertilizer (OLF) level on the production of fresh and dry matter, as well as organic matter of mini elephant grass (Pennisetum purpureum cv. Mott) in the second harvest. This research used a Completely Randomized Design (CRD) which consisted of 4 treatments and 4 replications to obtain 16 experimental units. The treatments were M0: without TOP G2 organic liquid fertilizer (OLF), M1: 10 ml TOP G2 OLF /1 water liter, M2: 20 ml TOP G2 OLF/1 water liter, M3: 30 ml TOP G2 OLF/1. The variables measured in this research are the production of fresh matter, dry matter and organic matter. The results of the analysis of variance showed that the treatment had no significant effect (P>0.05) on the production of fresh matter, dry matter and organic matter of mini elephant grass (Pennisetum purpureum cv. Mott) for the second harvest. The conclusion of this research is application of TOP G2 OLF at different level has relative same effect on the production of fresh matter, dry matter and organic matter of Mini Elephant Grass. M3 treatment (30ml / 1 liter of water) tends to provide the highest production of fresh matter, dry matter and organic matter.